Interfacial Polymetallic Oxides and Hierarchical Porous Core–Shell Fibres for High Energy‐Density Electrochemical Supercapacitors. (5th May 2022) - Wu, Guan; Ma, Ziyang; Wu, Xingjiang; Zhu, Xiaolin; Man, Zengming; Lu, Wangyang; Xu, Jianhong
Abstract: Realizing high energy‐density and actual applications of fibre‐based electrochemical supercapacitors (FESCs) are pivotal but challenging, as the ability to construct advanced fibres for accelerating charges kinetic diffusion and Faradaic storage remain key bottlenecks. Here, we demonstrate high‐performance FESCs based on hetero‐structured polymetallic oxides/porous graphene core–sheath fibres, where the large pseudo‐active polymetallic oxide (PMO) sheath is uniformly loaded on a hierarchical porous graphene fibre (PGF) core. Due to the abundant micro‐/mesoporous pathways, large accessible surface, excellent redox activity and good interface electron conduction, the PMO‐PGF possesses high areal capacitance (2959.78 mF cm −2 ) and manageable Faradaic reversibility in a 6 M KOH electrolyte. Furthermore, the PMO‐PGF‐based solid‐state FESCs present high energy‐density (187.22 μ Wh cm −2 ), long‐life cycles (95.8 % capacitive retention after 20 000 cycles), diverse‐powered capabilities and actual energy‐supply applications. Abstract : Hetero‐structured polymetallic oxides/porous graphene core–sheath fibres are demonstrated as high‐performance electrochemical supercapacitor electrodes via a microchannel self‐assembly method. Because of rich micro‐/mesoporous ionic pathways, a large accessible surface, high Faradaic activity and excellent interface electron conduction, the supercapacitors display remarkable areal capacitance, energy‐density, long‐life cycles and actual applications.